2014
DOI: 10.1186/2001-1326-3-24
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell delivery of therapies for brain disorders

Abstract: The blood brain barrier (BBB) poses a problem to deliver drugs for brain malignancies and neurodegenerative disorders. Stem cells such as neural stem cells (NSCs) and mesenchymal stem cells (MSCs) can be used to delivery drugs or RNA to the brain. This use of methods to bypass the hurdles of delivering drugs across the BBB is particularly important for diseases with poor prognosis such as glioblastoma multiforme (GBM). Stem cell treatment to deliver drugs to neural tumors is currently in clinical trial. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 98 publications
(128 reference statements)
2
61
0
1
Order By: Relevance
“…It was evidenced by PCR detection of the human albumin gene in rats receiving HUCBMSCs. These findings were in accordance with Aleynik et al [68] who reported stem cell homing to the brain. So, they can be the future form of treatment to bypass the blood brain barrier.…”
Section: Discussionsupporting
confidence: 83%
“…It was evidenced by PCR detection of the human albumin gene in rats receiving HUCBMSCs. These findings were in accordance with Aleynik et al [68] who reported stem cell homing to the brain. So, they can be the future form of treatment to bypass the blood brain barrier.…”
Section: Discussionsupporting
confidence: 83%
“…Specifically, they show migration towards pathology sites such as tumours/neurodegeneration (termed 'pathotropism') [8,9]. Intravenously delivered NSCs can cross the blood-brain barrier surrounding neural tissue into pathology foci -a phenomenon modulated by inflammation, astrocytosis and blood vessel formation -minimising adverse effects in surrounding normal host tissue [10].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies examining the effectiveness of stem cells overexpressing various growth factors to reduce degeneration neurons and improve clinical outcomes will help to maximize the positive effects of cell therapy. Furthermore, the affinity for stem cells, especially MSCs, to migrate to the brain make them attractive for gene and drug delivery [56]. In clinics, although the use of stem cell therapy for neurodegenerative diseases has gained considerable momentum in the recent past, there are still numerous hurdles that must be overcome.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%